-3-2 (4-1) simplified is -9
Answer:
Step-by-step explanation:
It is stated that a function rule takes an input, and converts it into an output, y, by decreasing twice the input by 4.
Let 'x' be the number
Decreasing twice the number 'x' by 4 = 2x-4
Now,
Given the input x = 5
As the output will decrease twice the input (x=5) by 4
Thus, the output = 2(5)-4 = 10-4 = 6
Therefore,
Answer:
those are pretty good! all a's and b's are good! Keep up the good work!!
Step-by-step explanation:
Answer:
I am pretty sure it is none of the above but I don’t know for sure
The answer is 18.2
I got the answer by solving it